Tailoring research articles to journals - Ting, Su Hie (Centre for Language Studies, 2014)
Knowing the written and unwritten rules of the game in getting journal papers published is necessary to compete for research space in the international research discourse community. This workshop aims to provide guidelines on tailoring research articles to journals to increase chances of getting journal papers published. The theoretical knowledge for the workshop is drawn from research on conventions of research articles and studies on why papers are accepted or rejected. The workshop begins with a review ofreasons for manuscript acceptance and rejection. This is followed by a presentation of how different parts of a research article are adjusted to fit targeted journals. Finally, several case studies are used to show how authors tailor their papers to targeted journals in terms of the relevance to the journal, novelty and soundness of research, methodological approach and, last but not least, the writing style and format requirements of journals. This workshop is designed to help participants develop a checking mechanism to ensure that their submissions are appropriate for the targeted journal and will get a fair chance ofreview. The workshop will benefit academics who are embarking on writing of research papers as well as academics accustomed to writing conference papers and who are venturing into journal paper writing.